Quantitative Analysis of HER2 Amplification by Droplet Digital PCR in the Follow-Up of Gastric Cancer Patients Being Treated with Trastuzumab after Surgery - Yanzhuo Liu; Maozhu Yang; Tao Jiang; Chunbin Lan; Hao Yuan; Guiquan Li; Guiqing Jia; Kang Wang; Gaoping Zhao (Gastroenterology Research and Practice)
Background. Circulating tumor DNA (ctDNA) derived from tumors is a promising biomarker for monitoring tumor status and evaluating therapeutic effects and prognosis. We studied the plasma human epidermal growth factor receptor 2 (HER2) amplification in gastric cancer (GC) patients by droplet digital PCR (ddPCR) during therapy with trastuzumab. Methods. A total of 12 patients were recruited after surgery. All patients received FOLFOX chemotherapy combined with trastuzumab as a treatment regimen. During the 12 months of the follow-up period, using elongation factor Tu GTP binding domain containing 2 (EFTUD2) as a reference gene, plasma HER2 to EFTUD2 ratios (the HER2 ratio) were determined for each patient every 2 months by ddPCR. Results. The concordance rate of HER2 amplification examined in plasma and formalin-fixed paraffin-embedded (FFPE) samples with ddPCR was 81.4%, with a sensitivity of 76.5% and a specificity of 83.8%. Plasma HER2 ratios were correlated with the primary tumor size (p<0.01). A significant decrease in the plasma HER2 ratio was found after two months of treatment (p<0.0001). Nine patients experienced partial response, and three patients had stable disease. Seven patients had progressive disease (PD) during follow-up, and four of them had died. The median progression-free survival (PFS) was 9.8 months. For each patient who developed PD, the plasma HER2 ratio was approximately 2.3-4.1 times higher than the cut-off value at the time of PD, which was the highest during the whole follow-up period. Conclusion. Longitudinal monitoring for the plasma HER2 ratio by ddPCR in the clinical courses of GC patients holds great promise for use as an indicator of tumor progression and treatment efficacy.